2014
DOI: 10.1175/jamc-d-14-0107.1
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality of the Urban Heat Island Effect in Madison, Wisconsin

Abstract: Spatial and temporal variation in the urban heat island (UHI) effect from March 2012 through October 2013 was characterized using continuous temperature measurements from an array of up to 151 fixed sensors in and around Madison, Wisconsin, an urban area of population 407 000 surrounded by lakes and a rural landscape of agriculture, forests, wetlands, and grasslands. Spatially, the density of the built environment was the primary driver of temperature patterns, with local modifying effects of lake proximity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
91
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 120 publications
(118 citation statements)
references
References 58 publications
9
91
1
3
Order By: Relevance
“…These experimental results show that road snow clearing has a stronger effect on T min than on T max (not shown), which is consistent with the results of Schatz and Kucharik (2014). This result also indicates that the decrease in T max is attributable mainly to snow cover on roofs.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…These experimental results show that road snow clearing has a stronger effect on T min than on T max (not shown), which is consistent with the results of Schatz and Kucharik (2014). This result also indicates that the decrease in T max is attributable mainly to snow cover on roofs.…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, snow cover in urban areas is of comparable importance to anthropogenic heat release when simulating the spatial air temperature contrast between urban and surrounding areas. Schatz and Kucharik (2014) reported snow depth effects on nocturnal surface air temperature through ground heat transfer change. To confirm the effect of snow depth and road snow clearing on urban surface air temperature, we conducted sensitivity experiments as the CL0, CL20, and NO_CL runs (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of the built-up environment manifests itself by impacting turbulent transport radiative heat exchange and hydrological processes, especially in urban canopies [36]. Schatz and Kucharik also demonstrated in their paper that the built-up environment was the primary driver of the spatial change in temperature patterns in the urban area [37]. They found that urban environments, together with their dark impervious surfaces and reduced vegetation cover, normally have large heat capacity and high thermal conductivity rates [34,[38][39][40][41][42].…”
Section: Discussionmentioning
confidence: 98%
“…For coastal environments, the enhanced UHI thermal gradient has been associated with the earlier onset of the sea breeze, followed by stagnation over the urban environment as the sea breeze is perturbed by the UHI circulation (Melas et al 2000;Khan and Simpson 2001;Lemonsu et al 2006b;Freitas et al 2007). Furthermore, enhanced convergence, vertical motion and aerosols concentrations from the UHI has been documented in association with increased cloud formation (Tsunematsu and Kai 2004;Schatz and Kucharik 2014), convective precipitation rates (Dixon and Mote 2003;Ryu et al 2015) and storm initiation (Rozoff et al 2003;Shem and Shepherd 2009). Continuing growth of the near-coastal urban landscape (Small and Nicolls 2003) highlights that UHI processes are increasingly a significant component of the coastal PBL.…”
Section: Planetary Boundary Layer Circulations and Convergence Zonesmentioning
confidence: 99%